Clinical researchImpact of morbid obesity on pulmonary function - Sekhri, Vishal; Abbasi, Faheem; Ahn, Chul W.; DeLorenzo, Lawrence J.; Aronow, Wilbert; Chandy, Dipak (Archives of Medical Science, 2008)
Introduction: While studies have examined the effects of mild-moderate obesity on pulmonary function, there have been no large studies that have specifically looked at the impact of morbid obesity, especially with regard to the influence of gender and age. Some studies have demonstrated an increased incidence of asthma among obese patients, suggesting that this may be due to a decrease in airway caliber, although there is little evidence to support this. The aim of this study was to examine the impact of morbid obesity on pulmonary function with a particular emphasis on the influence of gender and age. By including a large number of patients in the study, the goal was to also get some insight into the association between obesity and asthma. Material and methods: Pulmonary function test results were collected on 433 patients with a body mass index BMI ł40 kg/m 2 who were being evaluated for bariatric surgery between January 2001 and August 2006. Results: BMI had a significant impact on the forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), expiratory reserve volume (ERV), residual volume (RV), total lung capacity (TLC) and partial pressure of oxygen in arterial blood (PaO2). In addition, there were significant differences in pulmonary function based on the gender and age of the patient. FVC, FEV1, FEV1/FVC, ERV, TLC and PaO2 were all significantly reduced in males compared to females. Similarly, FVC was significantly reduced among subjects >40 years when compared to those Ł40 years. Conclusions: Our study demonstrated the effects of morbid obesity on pulmonary function. It also established the greater impact of obesity in men, which along with the absence of an obstructive impairment in almost all our patients suggests that asthma maybe being over-diagnosed in obese patients, especially women.